Relative Weight of Organic Waste Origin on Compost and Digestate 16S rRNA Gene Bacterial Profilings and Related Functional Inferences - Aigle, Axel; Bourgeois, Emilie; Marjolet, Laurence; Houot, Sabine; Patureau, Dominique; Doelsch, Emmanuel; Cournoyer, Benoit; Galia, Wessam (Frontiers in Microbiology, 2021)
Even though organic wastes (OWs) recycling via anaerobic digestion (AD) and composting are increasingly used, little is known about the impact of OWs origin (fecal matters, food and vegetable wastes) on the end products bacterial contents. The hypothesis of a predictable bacterial community structure in the end-products according to the OWs origin was tested. Nine OW treatment plants were selected to assess the genetic structure of bacterial communities found in raw OW according to their content in agricultural and urban wastes, and to estimate their modifications through AD and composting. Two main bacterial community structures among raw OWs were observed, and matched a differentiation according to the occurrences of urban chemical pollutants. Composting led to similar 16S rRNA gene OTU profiles whatever the OW origin. With a significant shift of about 140 genera (representing 50% of the bacteria), composting was confirmed to largely shape bacterial communities towards similar structures. The enriched taxa were found to be involved in detoxification and bioremediation activities. This process was found highly selective, and favorable for bacterial specialists. Digestates showed OTU profiles differentiated into two groups according to their relative content in agricultural (manure) and urban wastes (mainly activated sludge). About one third of the bacterial taxa was significantly affected by AD. In digestates of urban OW, this sorting led to an enrichment of 32 out of the 50 impacted genera, while for those produced from agricultural or mixed urban / agricultural OW (called central OW), a decay of 54 genera over 60 was observed. Bacteria from activated sludge appeared more fit for AD than those of other origins. Functional inferences showed AD enriched genera from all origins to share similar functional traits e.g., chemoheterotrophy, fermentation, while being often taxonomically distinct. The main functional traits among the dominant genera in activated sludge supported a role in AD. Raw OW content in activated sludge was found a critical factor for predicting digestate bacterial contents. Composting generated highly predictable and specialized community patterns whatever the OW origin. AD and composting bacterial changes were driven by functional traits selected by physicochemical factors such as temperature and chemical pollutants.